The role of thoracoscopic debridement in the treatment of parapneumonic empyema. (August 2013) - Bagheri, Reza; Tavassoli, Alireza; Haghi, Seyed Ziaollah; Attaran, Davoud; Sadrizadeh, Ali; Asnaashari, Amir; Basiri, Reza; Salehi, Maryam; Moghadam, Kamran Adhami; Tabari, Azadeh; Sheibani, Shima
Aim: To evaluate the efficacy of early video-assisted thoracoscopic debridement in patients with the fibropurulent phase of parapneumonic empyema. Patients and methods: 40 patients with parapneumonic empyema resistant to 2 weeks of antibiotic therapy, were randomly divided into 2 groups. In group 1 (20 patients), antibiotic therapy and irrigation was continued, and in group 2 (20 patients), video-assisted thoracoscopic debridement was performed. The 2 groups were compared in terms of therapeutic results. Results: The male/female ratio was 29/11. Group 1 included 16 men and 4 women with a mean age of 54 years, and mean hospital stay was 41 days. Group 2 consisted of 14 men and 6 women with a mean age of 51 years, and mean hospital stay was 23 days. Considering the therapeutic results, 12 patients in group 1 were cured by antibiotic therapy and irrigation, whereas 8 required decortication and pleurectomy with thoracotomy. In group 2, 18 patients were cured by video-assisted thoracoscopic debridement, and 2 underwent thoracotomy and decortication due to intraoperative bleeding. A significant difference in therapeutic results was noted between the groups ( p  = 0.028). Conclusion: Video-assisted thoracoscopic debridement provides a high success rate and less invasive treatment for the early stages of empyema.